2021
DOI: 10.1002/fes3.274
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide SNP discovery and QTL mapping for economic traits in a recombinant inbred line of Oryza sativa

Abstract: The objective of the study was to understand the genetic basis of eight traits conferring grain appearance and yield in a recombinant inbred line (RIL8) derived from a cross between cultivated Indica rice varieties Dexiang074B and Pujiang6. We conducted whole genome re‐sequencing for the two parental lines and genotyping by sequencing (GBS) for the RIL8 population. Next, we aligned the clean reads to the rice genome Nipponbare IRGSP 1.0, constructed the genetic linkage map (GLM), and performed the quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Third, some genes have negative effects on plant growth, yield, or quality (Xia et al, 2019). Our present study showed that hybrids from Dexiang074A (074A) could significantly enhance yield, quality, and drought tolerance (Figure 1; Li et al, 2021).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Third, some genes have negative effects on plant growth, yield, or quality (Xia et al, 2019). Our present study showed that hybrids from Dexiang074A (074A) could significantly enhance yield, quality, and drought tolerance (Figure 1; Li et al, 2021).…”
Section: Discussionmentioning
confidence: 61%
“…074B is a hybrid rice maintainer line with high combining ability as a parent, and 074A is the contra sterile line. 074B is used as a rice backbone parent line in Sichuan Province ( Li et al., 2021 ). The hybrid offspring of 074A have efficient nitrogen utilization, high grain quality, and drought resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Quality-related traits are complex traits that are influenced by a combination of multiple factors and genes and are susceptible to external environmental conditions, making it difficult to fully and truly evaluate the quality of rice with a single indicator 26 , 27 . PCA is a statistical analysis method that converts many indicators into a few composite indicators, making complex problems simple and their analysis intuitive through dimensionality reduction 9 , 10 .…”
Section: Discussionmentioning
confidence: 99%